Some research results of sediment accumlation rates on the prodelta of Mekong River Delta and the adjacent shelf - Thành, Nguyễn Trung; Phách, Phùng Văn; Anh, Lê Ngọc; Minh, Nguyễn Trung; Dũng, Bùi Việt; Long, Nguyễn Quang (Vietnam Journal of Earth Sciences, 2013)
Mekong River Delta, one of the largest deltas of Asia, has a high risk of flood due to the present sea level rise under the global climate warming. Therefore, the studies on Mekong River Delta evolution have been interested in the recent years, especially the subaqueous delta part, in which the land-ocean interaction takes place intensively. The sedimentation on the subaqueous delta and the adjacent shelf has an important significance in evaluating the development of the modern Mekong Delta and contributes to predict its future. However, the sedimentation research results on the subaqueous delta of Mekong River Delta and the adjacent shelf are still sparse. In this study, some features of geomorphology and geology of Mekong Delta were summarized and sediment accumulation rates at two points in the study area were calculated by measurement of radionuclides (210Pb, 226Ra, 137Cs). The sediment accumulation rate at the prodelta, southeast of Ca Mau Peninsular is 0.41 cm/year corresponding to mass accumulation rate 0.36g cm-2 year-1. The sediment accumulation rate on the shelf, southwestwards the study area is 0.14cm/year corresponding to mass accumulation rate 0.17 g cm -2 year-1.